2020
DOI: 10.3389/fmicb.2020.00771
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Ecology of Methanotrophy in Streams Along a Gradient of CH4 Availability

Abstract: Despite the recognition of streams and rivers as sources of methane (CH 4) to the atmosphere, the role of CH 4 oxidation (MOX) in these ecosystems remains poorly understood to date. Here, we measured the kinetics of MOX in stream sediments of 14 sites to resolve the ecophysiology of CH 4 oxidizing bacteria (MOB) communities. The streams cover a gradient of land cover and associated physicochemical parameter and differed in stream-and porewater CH 4 concentrations. Michealis-Menten kinetic parameter of MOX, max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Methylomirabilis sp. bacteria are restricted in using NO 2 − as an EA in CH 4 oxidation and have been reported to have a high affinity for CH 4 ( 10 , 28 ), Methylococcales are potentially capable of coupling CH 4 oxidation with fermentation and with reduction of a variety of EAs (e.g., O 2 , NO 3 − , NO 2 − , Fe 3+ , and organic EAs) and have a low affinity for CH 4 ( 11 19 , 26 , 27 ). This gives Methylococcales advantage over Ca .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylomirabilis sp. bacteria are restricted in using NO 2 − as an EA in CH 4 oxidation and have been reported to have a high affinity for CH 4 ( 10 , 28 ), Methylococcales are potentially capable of coupling CH 4 oxidation with fermentation and with reduction of a variety of EAs (e.g., O 2 , NO 3 − , NO 2 − , Fe 3+ , and organic EAs) and have a low affinity for CH 4 ( 11 19 , 26 , 27 ). This gives Methylococcales advantage over Ca .…”
Section: Resultsmentioning
confidence: 99%
“…capability for fermentation and anaerobic respiration of various EAs as explained above) than Ca . Methylomirabilis ( 12 , 15 , 17 , 18 , 26 28 ). Hence, it could be expected that changes in the OM quality of lake sediments affect differently the abundances of MOB and Ca .…”
Section: Introductionmentioning
confidence: 99%
“…Lower In freshwaters, a large fraction of CH4 in the aquatic food network exists as a carbon source which was oxidized by bacteria, can reduce CH4 entering the water by diffusion (Jones and Grey, 2011;Taipale et al, 2011;Frossard et al, 2015;Sawakuchi et al, 2016;Matoušů et al, 2019;Thottathil et al, 2019;Saarela et al, 2020), which may change CH4 dynamics in water. Previous studies reported that the methane oxidizing bacteria (MOB) can survive at oxic-anoxic interfaces in freshwater systems, and CH4 oxidation was frequently found in environments with high CH4 and DO concentrations (Bagnoud et al, 2020;Reis et al, 2020;Bai et al, 2021 (Whiticar and Faber, 1986;Conrad, 1999;Bastviken et al, 2002;Lima, 2005). The magnitude of δ 13 C-CH4 by MOB significantly depends on environmental conditions, so the fractionation factor (α) caused by microbial CH4 oxidation shows a large range of 1.003 to 1.039 (Templeton et al, 2006).…”
Section: Spatial and Temporal Variations In Ch4 And Co2 Concentrations δ 13 C-ch4mentioning
confidence: 99%
“…Lower In freshwaters, a large fraction of CH4 in the aquatic food network exists as a carbon source which was oxidized by bacteria, can reduce CH4 entering the water by diffusion (Jones and Grey, 2011;Taipale et al, 2011;Frossard et al, 2015;Sawakuchi et al, 2016;Matoušů et al, 2019;Thottathil et al, 2019;Saarela et al, 2020), which may change CH4 dynamics in water. Previous studies reported that the methane oxidizing bacteria (MOB) can survive at oxic-anoxic interfaces in freshwater systems, and CH4 oxidation was frequently found in environments with high CH4 and DO concentrations (Bagnoud et al, 2020;Reis et al, 2020;Bai et al, 2021). Moreover, the δ 13 C values of biogenic methane during methanogenesis were very low, such as methanogenesis by acetate fermentation in freshwaters, and the δ 13 C-CH4 was then gradually elevated during CH4 oxidation due to 13 C enrichment in residual CH4 (Whiticar and Faber, 1986;Conrad, 1999;Bastviken et al, 2002;Lima, 2005).…”
Section: Particulate Organic Matter and Stable Isotopic Signaturesmentioning
confidence: 99%